Application of Variable Infiltration Capacity Model (VIC) for Calculating Drought Indicators for Binh Thuan Province - Quang Hung, Nguyen; Duc Khanh, Le (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 1SDO - 10.25073/2588-1094/vnuees.4334, 2018)
Abtract: Drought is a complex natural hazard; so far, there have been several ways to assess drought levels using different indices. In this study, the Variable Infiltration Capacity (VIC) model was used to calculate the relative changes of soil moisture in Binh Thuan province based on surface-subsurface water exchange processes. Model results are then used to quantify drought indicators for assessment of drought situations in Binh Thuan province. Modeled results show that drought occurrences in the study basin are high and complicated, clearly indicating the effect of rainfall, temperature and vegetation cover to water exchange and soil moisture. This work demonstrates the applicability of VIC model for the development of drought forecasting tools for agricultur and water resources planning. Keywords: Drought, VIC model, relative soil humidity, Bình Thuận. References: [1] Liang, X., D. P. Lettenmaier, E. F. Wood, and S. J. Burges (1994), A simple hydrologically based model of land surface water and energy fluxes for general circulation models, J. Geophys. Res., 99(D7), 14415–14428, doi:10.1029/94JD00483. [2] Bowling, L., et al. (2008), Current capabilities in soil thermal representations within a large scale hydrology model, in 9th International Conference on Permafrost, edited, Fairbanks, AK. [3] Bowling, L., et al. (2008), Current capabilities in soil thermal representations within a large scale hydrology model, in 9th International Conference on Permafrost, edited, Fairbanks, AK. [4] Maurer, E. P., et al. (2002), A long-term hydrologically based dataset of land surface fluxes and states for the conterminous United States, J. Clim., 15(22), 3237-3251. [5] Nijssen, B., et al. (2001b), Global retrospective estimation of soil moisture using the variable infiltration capacity land surface model, 1980-93, J. Clim., 14(8), 1790-1808. [6] Maurer, E. P., et al. (2002), A long-term hydrologically based dataset of land surface fluxes and states for the conterminous United States, J. Clim., 15(22), 3237-3251. [7] Zhu, C. M., and D. P. Lettenmaier (2007), Long-term climate and derived surface hydrology and energy flux data for Mexico: 1925-2004, J. Clim., 20(9), 1936-1946. [8] Lohmann, D., et al. (1998a), Regional scale hydrology: I. Formulation of the VIC-2L model coupled to a routing model, Hydrol. Sci. J.-J. Sci. Hydrol., 43(1), 131-141. [9] Nguyễn Lương Bằng, Trần Quốc Lập (2014),Ứng dụng mô hình VIC trong đánh giá hạn hánở lưu vực sông Cái, Tạp chí Khoa học kỹ thuật Thủy lợi và Môi trường - số 46 (9/2014). [10] Phạm Quang Vinh, Phạm Thị Thanh Hương (2012), Đánh giá hạn nông nghiệp tỉnh Bình Thuận theo kịch bản Biến đổi khí hậu, Tạp chí Các khoa học về trái đất, 34(4), 513-523. [11] Ngô Thanh Sơn và nnk (2018), Đánh giá tình hình hạn hán tại tỉnh Bình Thuận giai đoạn 1984-2016,Tạp chí Khoa học Nông nghiệp Việt Nam 2018, 16(4): 339-350.